Expression of the proteasome activator PA28 rescues the presentation of a cytotoxic T lymphocyte epitope on melanoma cells - Sun, Yuansheng; Song, Mingxia; Paschen, Annette; Schadendorf, Dirk (Cancer research, 2002)
The proteasome system represents a major source of HLA class I- presented peptides exposed to CTLs. Stimulation of cells with IFN-γ instantly induces the expression of the proteasome immunosubunits as well as the proteasome activator PA28. These proteins have been shown to optimize class I antigen presentation of several viral CTL epitopes; however, their contribution to tumor antigen processing remains poorly understood. Here, we analyzed the generation of an HLA-A*0201-presented epitope derived from the melanoma antigen tyrosinase-related protein 2 (TRP2). Melanoma cells that lacked the IFN-γ-inducible proteasome activator PA28 and immunoproteasomes did not display the TRP2360-368 epitope to specific CTLs. Our experiments demonstrate that epitope presentation correlated with the presence of PA28 and could be completely rescued by restoration of PA28 expression. In vitro digestion of TRP2 polypeptides with 20S proteasomes confirmed that PA28 is essential for epitope liberation. Thus, our experiments indicate that PA28 provides the threshold for CTL recognition of this epitope. Importantly, processing of a second TRP2-derived epitope, TRP2288-296, was diminished in IFN-γ-treated cells, even in the absence of immunoproteasome up-regulation. Therefore, the reported IFN-γ-induced self-regulation of epitopes may not necessarily be a consequence of immunoproteasomes as suggested previously.
Gesehen am 11.11.2020